Werewolves in the immunitary paradigm - Torrano, María Andrea (2016)
This article problematizes the political category of the monster in Hobbes's thought from a biopolitical perspective. Even though political thought has been tra-ditionally focused on Leviathan's figure as a political monster, here we pay particular attention to the maxim homo homini lupus, which can be identified with the wereWolf. This figure allows us on the one hand, to show how the Wolf becomes man with the creation of the State, and on the other hand, to show how there is a constant threat of man becoming Wolf, of the lupification of man. Hobbes's discourse of sovereignty aims to neutralize the wereWolf. This neutralization can be seen as immunization. In this sense, the wereWolf operates both as poison and as antidote-pharmakon-within the State. The wereWolf produces an inoculation with a therapeutical function: it is a dose of the same poison from which the State seeks to protect itself.